COVID-19 and armed conflict. (April 2021) - Ide, Tobias
Highlights: COVID-19 has affected armed conflict dynamics by changing the strategic environment for armed groups. Armed conflict escalation is more likely than de-escalation in the face of the pandemic. Armed conflict de-escalation occurred in the face of COVID-19 in some countries. Grievances and health diplomacy have so far only played a minor role. Abstract: This article studies the impact of COVID-19 on armed conflict. The pandemic has significant health, economic and political effects. These can change the grievances and opportunity structures relevant for armed conflicts to either increase or decrease conflict risks. I analyse empirical evidence from Afghanistan, Colombia, India, Iraq, Libya, Pakistan, the Philippines, Thailand and Yemen from the first six months of 2020. Results suggest that COVID-19 provides little opportunities for health diplomacy and cooperation, but it also has not yet driven grievances to a level where they became relevant for armed conflicts. Four countries have encountered temporary declines in armed conflicts, mostly due to strategic decisions by governments or rebels to account for impeded logistics and to increase their popular support. Armed conflict levels have increased in five countries, with conflict parties exploiting either state weakness or a lack of (international) attention due to the COVID-19 pandemic. This is a worrisome trend given the tremendous impacts of armed conflict on human security and on the capabilities of countries to deal with health emergencies.